Antimicrobial Activity against Oral Pathogens Confirms the Use of Musa paradisiaca Fruit Stalk in Ethnodentistry. (6th September 2021) - Owusu-Boadi, Ernest; Akuoko Essuman, Mainprice; Mensah, Gabriel; Ayamba Ayimbissa, Emmanuel; Boye, Alex
Abstract : Background . Ethnodentistry is the use of indigenous oral cleansing agents such as plant parts by local folks not only to maintain oral hygiene but also to treat oral infections. Mostly, ethnodentistry is inspired by traditions and belief systems of local communities. Musa paradisiaca is extensively cultivated and used in many cultures for its nutritional and medicinal values. In Ghana, the fruit stalk of Musa paradisiaca is used as an oral cleansing agent to maintain oral hygiene; yet this folk claim remains to be ascertained scientifically. Objective . The study assessed the antibacterial and antifungal effects of three extract fractions (aqueous, ethanol, and ethyl acetate fractions) of Musa paradisiaca fruit stalk against Lactobacillus acidophilus, Aggregatibacter actinomycetemcomitans, and Candida albicans, common oral pathogens implicated in dental caries and periodontitis. Materials and Methods . Aqueous, ethanol, and ethyl acetate fractions of Musa paradisiaca fruit stalk were prepared by cold maceration and qualitatively screened for their phytochemical composition. Antimicrobial effects of the three extract fractions were assessed by using serial broth dilutions at increasing concentrations (62.5, 125, 250, 500, and 1000 µ g/ml) and compared to standard antimicrobial agents (erythromycin, doxycycline, and fluconazole). Subsequently, the absorbances of the microbial suspensions treated with increasing concentrations of the extract fractions were measured at 450 nm, and the cell densities were determined. Results . Except for the aqueous extract, which was less effective in decreasing microbial growth, the ethyl acetate and the ethanol extract fractions demonstrated antimicrobial efficacies comparable to those of the standard drugs. All three extract fractions demonstrated concentration-dependent growth inhibitory effects on the tested oral pathogens although not as effective as the standard drugs used. Conclusion . Musa paradisiaca fruit stalk has demonstrated antimicrobial effects against Lactobacillus acidophilus, Aggregatibacter actinomycetemcomitans, and Candida albicans, common oral pathogens implicated in dental caries and periodontitis, and this finding confirms in part folk use of Musa paradisiaca fruit stalk as a traditional dental care agent. Thus, the fruit stalk of Musa paradisiaca could be explored for use as a cheap and readily available dental care agent for people entrapped in the poverty line.